1993
DOI: 10.1149/1.2056091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurities on the Luminescence Quantum Efficiency of  ( La , Ce , Tb )  PO 4

Abstract: The influence of impurities on the luminescence quantum efficiency of La0v~Ce0.~PO4 and La0.35Tb0 ~PO4 has been studied. The transition metal ions Fe and Mn are not built into the LaPO~ lattice under a reducing firing atmosphere. 4+Tetravalent Ce is probably present in a second phase. Codoping with cations with different valencies has no influence onthe Ce amount nor on the Ce quantum efficiency. The energy transfer rate from Ce to a number of rare-earth ions (Pr , Nd ~+, Dy ~+, Ho ~+, Er 3+) is low. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 4 publications
5
65
1
2
Order By: Relevance
“…35 Luminescence quenching of this kind has been shown to occur, for instance, in bulk LaPO 4 :Tb codoped with rare-earth ions such as Nd 3+ , Ho 3+ , Pr 3+ , or Er 3+ . 32 Pure LaPO 4 :Tb shows a single-exponential luminescence decay with a lifetime of 3.2 ms. Both the luminescence kinetics and the lifetime are reported to remain unchanged even at high terbium concentrations, indicating the absence of energy migration over the Tb 3+ ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Luminescence quenching of this kind has been shown to occur, for instance, in bulk LaPO 4 :Tb codoped with rare-earth ions such as Nd 3+ , Ho 3+ , Pr 3+ , or Er 3+ . 32 Pure LaPO 4 :Tb shows a single-exponential luminescence decay with a lifetime of 3.2 ms. Both the luminescence kinetics and the lifetime are reported to remain unchanged even at high terbium concentrations, indicating the absence of energy migration over the Tb 3+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…33 The cerium absorption band shows a weak extension from about 300 to 450 nm, which is caused by the presence of a small amount of Ce 4+ . 32 The luminescence spectrum in Figure 5 shows the typical line spectrum of the terbium 5 D 4 -7 F J transitions between 450 and 700 nm. 34 Since in the case of terbium not only the 7 F J states but also the 5 D 4 state is split into several sublevels by the crystal field, each peak in the spectrum consists of a large number of unresolved lines.…”
Section: Resultsmentioning
confidence: 99%
“…7 F J relaxation takes place. Despite luminescence properties of bulk LaPO 4 :Ce,Tb, as well as energy transfer processes between Ce 3þ and Tb 3þ ions, which have been intensively studied before, 34,[39][40][41][42] we have recently suggested alternative mechanism of energy transfer via the so-called impurity trapped exciton states in nanosized LaPO 4 :Ce,Tb 43 by analogy with some other wide bandgap materials. [44][45][46] Most of the studies reported in the literature were performed using laser or ultraviolet lamps as an excitation sources, while, for instance, LaPO 4 belongs to the class of wideband-gap materials, and its experimental bandgap was reported to be around 8.0 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular commercialized phosphors using for FLs consist of the blue-emitting BaMgAl 10 O 17 : Eu 2þ [1], the green-emitting LaPO 4 : Ce 3þ , Tb 3þ [2] and the red-emitting Y 2 O 3 : Eu 3þ [3] oxides. Although the basics of industrial-scale phosphor synthesis had been well-established for a decade, application that employs red oxide phosphor has suffered from problems such as low color purity and high cost [4].…”
Section: Introductionmentioning
confidence: 99%